The complete mitochondrial genome of Cerceris quinquefasciata (Hymenoptera: Crabronidae) - Li, Xiao-Li (Mitochondrial DNA B Resour, 2021)
The complete mitochondrial genome of the Cerceris quinquefasciata (Rossi, 1792) (Hymenoptera: Crabronidae) was obtained via next-generation sequencing. This mitochondrial genome is 16,188 bp in length with 37 classical eukaryotic mitochondrial genes and two A + T-rich region. All the 13 PCGs begin with typical ATN codons. Among them, eleven PCG genes terminate with TAA, two with T–. All of the 22 tRNA genes, ranging from 58 to 72 bp with typical cloverleaf structure except for trnS1, whose dihydrouridine (DHU) arm forms a simple loop. Phylogenetic analysis highly supported Crabronidae is the sister group of anthophila bees.